Bukit Antarabangsa: a legal review of the landslide turmoil / Amalina Yasmin Mohd. Sokri ...[et al.] - Mohd. Sokri, Amalina Yasmin; Mohd. Zawawi, Anis Syazween; Mohd. Azmi, Hilda Hayat; Zainal, Noor Izzati (2009)
This research paper encompasses legal aspect of hill slope development in Malaysia. Following the most recent case of Bukit Antarabangsa landslide occurrence on the 6th of December 2008, this research is most concerned on the identification of the laws available governing hill slope development as well as the responsible bodies in authority involved with regards to the matter. Subsequently, the research paper analyses whether there are any loopholes in the concerned law. The statutes identified and discussed include Town and Country Planning Act 1976, Environmental Quality Act 1974, Street, Drainage and Buildings Act 1974 and National Land Conservation Act 1960. In spite of having all the statutes to govern hill slope development, landslides still occur. This shows that the enforcement of laws are less effective. With regards to the lacking of enforcement of laws, the recommendations are to amend the existing provisions of statutes as well as one specific Act should be proposed to govern hill slope development. The laws in Hong Kong are reviewed whereby they have a well structured management on landslide prevention. There is one single institution called Geotechnical Engineering Office to regulate geotechnical engineering and enforce the slope safety system in Hong Kong. The risk of landslide has been successfully reduced ever since the system was put into effect after the establishment of the GEO in 1977. With this, the situation in Hong Kong has been put forward in the recommendation to achieve a proper and effective management of the hill slope development.